They Are Coming Home: The Effect of Trauma-Related Cognitions on Vocational Readiness of Incarcerated Women - Anderson, Joi D. (Journal of interpersonal violence, 2021)
The prevalence of trauma in the lives of incarcerated women has been well-documented. Yet, few studies have included trauma-related cognitions, a common response to interpersonal trauma, in their analyses. The purpose of this study was to examine the relationship between trauma (pre-incarceration trauma [PIT] and incarceration-based trauma [IBT]), trauma-related cognitions [TRC] (i.e., Total; Self, Blame, and World), posttraumatic stress disorder (PTSD) severity, and vocational readiness-motivation (VR-M) in a random sample of incarcerated women in three prison facilities. A cross-sectional research design was employed using a stratified random sampling procedure. The stratum was housing security levels 1 to 4. The study was conducted in three prisons located in the midwestern region of the United States. Self-administered questionnaires measured PIT, IBT, TRC, PTSD, and VR-M. The study sample included (N = 250) female inmates: 152 White (60.8%), 50 Black (20.4%), 18 Biracial (7.3%), 13 Native American/Pacific Islander (5.3%), and 12 Latina (4.8%) females. The average age of participants was 36.2, and 82.4% were mothers. A key finding in this study was that TRC-Total was best predicted by trauma associated with the prison environment (IBT) and PTSD severity. Our findings indicated that for Black and Latina women, higher levels of trauma-related cognitions about “self” were predictive of a lower potential for vocational readiness in the area of motivation. Future examination of trauma’s effect on the development of negative trauma-related cognitions about self (e.g., self as incompetent) has the potential to inform prison mental health practice and the development of clinical interventions to decrease trauma-related cognitions about self for incarcerated women with multiple trauma experiences.